1998
DOI: 10.1080/00480169.1998.36044
|View full text |Cite
|
Sign up to set email alerts
|

The prophylactic effect of a teat sealer on bovine mastitis during the dry period and the following lactation

Abstract: Closure of the teat canal from day one of the dry period as achieved by the teat sealer was as effective in reducing new dry period infections as the infusion of a long-acting dry cow antibiotic formulation. The lower incidence of new infections in the ensuing lactation among the infused quarters implies that fewer subclinical infections persisted from the dry period. Use of teat sealers at drying off appears to offer the same prophylactic efficacy as the dry cow antibiotic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
104
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 5 publications
10
104
2
1
Order By: Relevance
“…While considering clinical mastitis at animal level; 4 animals (40%) out of 10 had clinical mastitis. Our observations are in consonanace with those reported by Woolford et al (1998), who observed 2.3 and 13% infection at calving (at quarter level), respectively in cows with and without DCT. McDougall (2010) observed that 9% of uninfected and untreated glands developed new intra-mammary infections over the dry period in pasture-grazed cows, compared to 2-2.5% protected by antibiotic DCT.…”
Section: Results and Discussion Incidence Of Clinical Mastitissupporting
confidence: 81%
“…While considering clinical mastitis at animal level; 4 animals (40%) out of 10 had clinical mastitis. Our observations are in consonanace with those reported by Woolford et al (1998), who observed 2.3 and 13% infection at calving (at quarter level), respectively in cows with and without DCT. McDougall (2010) observed that 9% of uninfected and untreated glands developed new intra-mammary infections over the dry period in pasture-grazed cows, compared to 2-2.5% protected by antibiotic DCT.…”
Section: Results and Discussion Incidence Of Clinical Mastitissupporting
confidence: 81%
“…The data from these trials were evaluated for incidence of new intramammary infections, clinical infections and cure rate of existing infections. These data were also compared with data from the literature (Neave et al 1950 ;Eberhart & Buckalew, 1972 ;Woolford et al 1998;Hassan et al 1999).…”
Section: Probability Estimationmentioning
confidence: 98%
“…Again, cows were randomly allocated within cell count groups to treatment groups. Data from the literature were used as both a source and to confirm some of the physiological effects and economic values that were derived from the above two studies (Neave et al 1950 ;Eberhart & Buckalew, 1972 ;Houben et al 1993 ;Houben et al 1994 ;Woolford et al 1998;Hassan et al 1999;Yalcin et al 1999;Yalcin & Stott, 2000 ;Huxley et al 2002). Data were adjusted where possible for the UK situation and values are in pounds sterling.…”
Section: Probability Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to previous reports on the incidence of new IMI and prevalence of Strep. uberis in the dry period (Woolford et al, 1998;Berry and Hillerton, 2002). Up to 50% of enterobacterial CM cases that occur within the first 100 DIM arise in quarters that were already infected during the dry period (Bradley and Green, 2000).…”
Section: Discussionmentioning
confidence: 99%